International Law Non-Compliance: Assessing Uruguay’s Decision to Legalize Cannabis under Jose Mujica Regime - Tesalonika, Novia Sinta; Kusumawardani, Natasya (President University, 2018)
Uruguay has ratified the international drug control conventions that consist of Single Convention on narcotic drugs 1961 as amended 1972 protocol, the convention on psychotropic substance 1971, and United Nations Convention against Illicit Traffic in Narcotic Drugs and Psychotropic Substances 1988. Since then, the Uruguayan government has been a part of the ‘War on Drugs